SLUG - Rodrigues, Nuno M. (2022)
Rodrigues, N. M., Batista, J. E., La Cava, W., Vanneschi, L., & Silva, S. (2022). SLUG: Feature Selection Using Genetic Algorithms and Genetic Programming. In E. Medvet, G. Pappa, & B. Xue (Eds.), Genetic Programming: 25th European Conference, EuroGP 2022, Held as Part of EvoStar 2022, Madrid, Spain, April 20–22, 2022, Proceedings (pp. 68-84). (Lecture Notes in Computer Science; Vol. 13223). Springer. https://doi.org/10.1007/978-3-031-02056-8_5 -------------------------------------------------------------------This work was supported by FCT, Portugal, through funding of LASIGE Research Unit (UIDB/00408/2020 and UIDP/00408/2020); MAR2020 program via project MarCODE (MAR-01.03.01-FEAMP-0047); projects BINDER (PTDC/CCI-INF/29168/2017), AICE (DSAIPA/DS/0113/2019), OPTOX (PTDC/CTA-AMB/30056/2017) and GADgET (DSAIPA/DS/0022/2018). Nuno Rodrigues and João Batista were supported by PhD Grants 2021/05322/BD and SFRH/BD/143972/2019, respectively; William La Cava was supported by the National Library Of Medicine of the National Institutes of Health under Award Number R00LM012926.